Covid In Parenteral Viral Hepatitis 19 Forgiveness of Infection - Mirzaeva Shahodat Boynazarovna (Genius Journals, 2022)
This article provides information on the course, clinical manifestations, treatment stages and immunity of Covid 19 infection in patients with parenteral viral hepatitis.
Keywords: Viral hepatitis; HBV; HCV; HDV